Developing e-resources utilisation strategies for Tanzanian higher learning institutions: a case of Mzumbe University - Mosha, Goodluck E.; Siyao, Peter O.; Nyakwaka, David O. (Dar es Salaam University Press (DUP), 2024)
Conference paper submitted to the 3rd COTUL Scientific Conference Heal at Moshi Cooperative University 2021